Concurrent and real-time programming in java: threads, RTSJ and RMI - Benmammar, Badr (Wiley-Blackwell, 2018)
Providing an introduction to concurrent, real-time, distributed programming with Java object-oriented language support as an algorithm description tool, this title describes in particular the mechanisms of synchronisation (cooperative and competitive) and sharing of data (internal class, static variables) between threads in Java. He then discusses the use of Java for real-time applications. Consequently, a presentation of the RTSJ (Real Time Specification for Java) specification dedicated to the development of real-time applications in Java is also introduced in this book. Finally, a presentation of programming distributed in Java is presented.